Investigation and analysis of the impact of historical contexts on urban tourism development - Ali Morvati (اکولوژی انسانی)
The purpose of this research is to investigate the role of historical contexts in the tourism development of Gamishan city and to identify the challenges facing it. The scope of the study includes the historical contexts of this city and our statistical community, local residents, tourism managers, and tourists. The research sample consists of 150 people who will be selected using random sampling method. In this research, a mixed method (qualitative and quantitative) is used, and the research tools include questionnaires designed to collect statistical data and semi-structured interviews with tourism experts and experts. The innovation of this research is in the integration of historical and cultural aspects with the development of sustainable tourism in the region and providing operational solutions to improve tourist attraction. The results show that the historical contexts not only act as a source of attraction for tourists, but also, if properly managed, can contribute to the economic and social development of the region. Also, challenges such as the negative effects of tourism on the local community and the deterioration of cultural heritage have also been identified. These cases require comprehensive management and empowerment of local communities to lead to the preservation and optimal exploitation of this historical heritage.